Approximation with Chlodowsky-Sheffer Operators on Unbounded Intervals - Ozarslan, Mehmet Ali; Cekim, Bayram; Cit, Sezin (Springer Basel Ag, 2025)
In this paper, we introduce some operators based on binomial operators involving Sheffer polynomials, which allows us to approximate continuous functions on unbounded intervals. We investigate the approximation properties of the operators in weighted spaces. With the help of the first and second modulus of continuity, we obtain the degree of approximation of continuous functions using Petree's kappa-functional. We also find the approximation degree for functions of the modified Lipschitz class. Eventually, according to the choices of the generating function h(t), the operator includes Laguerre-type, Bell-type, and Chlodowsky-type operators in special cases. We illustrate the approximation of these special cases for some functions. Finally, we give the generalization of the operator.
Keywords: Chlodowsky-Sheffer operators; modulus of continuity; Sheffer polynomials; Sheffer polynomials; Petree's kappa-functional